Recent advancements in the molecular biology of pituitary adenomas. Issue 4 (4th July 2022) - Zheng, Allison C.; Wang, Elaina J.; Aghi, Manish K.
ABSTRACT: Introduction: Pituitary adenomas are a common and diverse group of intracranial tumors arising from the anterior pituitary that are usually slow-growing and benign, but still pose a significant healthcare burden to patients. Additionally, they are increasing in both incidence and prevalence, leading to a need for better understanding of molecular changes in the development of these tumors. Areas covered: A PubMed literature search was conducted using the terms 'pituitary adenoma' in combination with keywords related to secretory subtype: lactotroph, somatotroph, corticotroph, gonadotroph and null cell, in addition to their transcription factor expression: PIT1, TPIT, and SF-1. Articles resulting from this search were analyzed, as well as relevant articles cited as their references. In this review, we highlight recent advances in the genetic and epigenetic characterization of individual pituitary adenoma subtypes and the effect it may have on guiding future clinical treatment of these tumors. Expert opinion: Understanding the molecular biology of pituitary adenomas is a fundamental step toward advancing the treatment of these tumors. Yet crucial knowledge gaps exist in our understanding of the underlying molecular biology of pituitary adenomas which can potentially be addressed by turning to differentially activated molecular pathways in tumor relative to normal gland.